All‐Dielectric Frequency Selective Surface Based on 3D Printing Materials (Phys. Status Solidi A 14∕2018). Issue 14 (24th July 2018) - Li, Liyang; Wang, Jun; Feng, Mingde; Du, Hongliang; Ma, Hua; Wang, Jiafu; Zhang, Jieqiu; Qu, Shaobo
Abstract : 3D Printing Materials 3D Printing all‐dielectric frequency selective surface is proposed and fabricated. Microwave transparent low permittivity materials can be used to realize bandstop frequency selective surface (FSS). 3D printing method promotes a rapid fabrication of FSS in flexible shapes and large scales. Future studies in different low permittivity dielectric materials may capable to support flexible design of multi‐functional FSS. More details can be found in article number1700840 by Liyang Li, Jun Wang, Mingde Feng, Shaobo Qu and co‐workers.